Lurasidone for the Treatment of Schizophrenia: Design, Development, and Place in Therapy - Miura I; Horikoshi S; Ichinose M; Suzuki Y; Watanabe K (Dove Medical Press, 2023)
Itaru Miura,1 Sho Horikoshi,1,2 Mizue Ichinose,1,3 Yuhei Suzuki,1 Kenya Watanabe4 1Department of Neuropsychiatry, Fukushima Medical University School of Medicine, Fukushima, Japan; 2Department of Neuropsychiatry, Horikoshi Psychosomatic Clinic, Fukushima, Japan; 3Department of Neuropsychiatry, Hoshigaoka Hospital, Koriyama, Japan; 4Department of Pharmacy, Fukushima Medical University Hospital, Fukushima, JapanCorrespondence: Itaru Miura, Department of Neuropsychiatry, Fukushima Medical University School of Medicine, Hikarigaoka 1, Fukushima, 960-1295, Tel +81-24-547-1331, Fax +81-24-548-6735, Email itaru@fmu.ac.jpAbstract: This review aims to provide a comprehensive overview of the current literature on the drug design, development, and therapy of lurasidone for the treatment of schizophrenia. Lurasidone has antagonistic effects on the dopamine D2, 5-hydroxytryptamine (5-HT)2A, and 5-HT7 receptors and a partial agonistic effect on the 5-HT1A receptor with low affinities for muscarinic M1, histamine H1, and a1 adrenergic receptors. The receptor-binding profile of lurasidone is thought to be associated with fewer side effects such as anticholinergic effects, lipid abnormalities, hyperglycemia, and weight gain. Behavioral pharmacological studies have demonstrated that lurasidone exerts anxiolytic and antidepressive effects and improves cognitive function, which are associated with the modulation of 5-HT7 and 5-HT1A receptors. Literature search using PubMed was performed to find published studies of randomized controlled trials and recent meta-analyses regarding efficacy and safety, particularly metabolic side effects of lurasidone in schizophrenia. In short-term studies, the results of randomized placebo-controlled trials and meta-analyses have suggested that lurasidone was superior to placebo in improving total psychopathology, positive symptoms, negative symptoms, and general psychopathology in patients with acute schizophrenia. Regarding safety, lurasidone had minimal metabolic side effects, and was identified as one of the drugs with the most benign profiles for metabolic side effects. Long-term trials revealed that lurasidone had the preventive effects on relapse, with minimal effects on weight gain and other metabolic side effects. Furthermore, lurasidone improves cognitive and functional performance of patients with schizophrenia, especially in long-term treatment. Patients with schizophrenia require long-term treatment with antipsychotics for relapse prevention; thus, minimizing weight gain and other side effects is crucial. Lurasidone is suitable as one of the first-line antipsychotic drugs in the acute phase, and a switching strategy should be considered during the maintenance phase, to balance efficacy and adverse effects and achieve favorable outcomes in the long-term course of schizophrenia.Keywords: schizophrenia, lurasidone, serotonin-dopamine antagonist, antipsychotics